Quantitative analysis of product categorization in soft drinks using bottle silhouettes (2015)
In our daily life, we use our senses to acquire information about the objects that surround us. However, the information processing that allows for the recognition and consecutive classification of those objects into categories remains unclear. Our purpose is to analyze the categorization mechanism taking into account: (a) package visual metrics and (b) consumer perceptions of this basic visual information. First of all, we quantitatively analyzed the physical characteristics of 52 bottle silhouettes of seven soft drink categories: sports drinks, water, flavored water, sodas, fruit juices, malt drinks and tea. We found that measures of the shape of the bottles can model the membership to a product category. Our first experiment tested how accurately consumers could recognize product category from real bottle silhouettes. We found that the visual characteristics that differentiate product category silhouettes are lid width and bottle shape (body kurtosis). Our second experiment tested the capacity of consumers to recognize artificially created bottle silhouettes. When basic information, such as the product shape is modified, consumers are not always capable of recognizing its corresponding category. We concluded that the physical attributes of bottles are related to the categorization process of the bottle content made by consumers. These findings may provide guidelines for new bottle designs that capitalize on existing categorization rules based on consumer perception.